Behaviour Pattern of Musth and NON Musth in Captive Asian Elephant - Sathasivam S (Department of Livestock Production Management, College of Veterinary and Animal Sciences, 2004)
Adult male elephants live in a highly dynamic world of changing sexual state, rank, association and behaviour. Physiologically musth is known to be associated with the elevated testosterone levels. There is a positive relationship between changes in testosterone and musth related behaviour, which make the animal in physiological stress. Captive male Asian elephants maintained in the elephant camp at Punnarthurkotta were utilized for the study. Experimental animals were grouped into normal, pre-musth, musth and post-musth stages. A total of 193 hours of observation were carried out by focal animal sampling technique using a behaviour score sheet. Faecal samples were collected from each animal in all stages and stored at –200 c, until it was extracted for measurement of faecal testosterone by RIA technique.